Processing and Added Value of Bamboo in Tasikmalaya, West Java - Tri Sulistyati Widyaningsih; Eva Fauziyah; Devy Priambodo Kuswantoro (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2020)
Bamboo is a multipurpose plant that has been used by the people for generations. This study aimed to describe the processing of bamboo and analyze its added value in Tasikmalaya Regency, West Java. Data was collected in April -December 2016 through interviews using questionnaires and field observations of bamboo craftsmen, and then were processed and analyzed quantitatively and descriptively. The community processed bamboo into woven products such as ayakan, boboko, haseupan, hihid, picnic basket, nyiru, pipiti, and parcel, as well as non-woven products such as piggy banks, key chains, glasses, wall clocks, lampshades, invitation boxes, bowl, cup, frame, teapot, letterbox, and tissue box. The average added value of woven products was IDR 131,197.21 or 9.11 % of the non-woven products, which was IDR 1,439,742.42. The average added value ratio of woven products is 0,83 and 0,90 for non-woven products. Bamboo woven business for household products is mostly done because the market has formed, stable, and has a wider scope even though it has lower added value. The market of non-woven products is smaller and specific even though it has a higher added value. A bamboo stem is only valued IDR 10,000 – 50,000, so it should be sold in processed products rather than the original form.Keywords: bamboo, processing, added value, woven, non-woven